Implementación de la NIC 41 activos biológicos, en la hacienda bananera denominada cooperativa de producción y comercialización la Clementina, parroquia la unión, cantón Babahoyo y su afectación en el manejo de las exportaciones en el año 2016 - Balseca Jurado, Sandra Elizabeth (2016)
This research was conducted in the banana plantation called Cooperative Production and Marketing Clementina Parish Union, Canton Babahoyo which allowed us to establish the accounting treatment and subsequent presentation and disclosure in the financial statements for agricultural activity, for which with the contribution of financial staff and endorsement owner of the hacienda of the presentation of the financial Information Biological Assets has analyzed the difference that determines the application of the International Accounting Standard IAS 41 in the financial Statements was found and it was determined the change that the implementation of the International Accounting Standard (IAS) 41 in the structuring of financial statements. To achieve the expected results of the investigation, several, including inductive, deductive, scientific and technical research methods such as observation, document review, interview with the manager of the estate, surveys of the 10 people involved in a used or otherwise with the handling of financial information. With the information gathered, we proceeded to analyze and interpret it, discovering that much of the financial staff of the hacienda known about the applicability of IFRS and specifically IAS 41 Biological assets. Additionally, the demonstration of the hypothesis was conducted using the statistical model Chi-Square, it discovered that the accepted hypothesis is: "The implementation of IAS 41 Biological assets SI enable improved management of production and exports banana plantation called Production and Marketing Cooperative Clementina" and proper preparation of financial statements. Among the most important recommendations it is contemplated to carry out and implement a training plan staff financial and administrative area of the banana plantation called Cooperative Production and Marketing Clementina, related to processes, regulations, adoption of IFRS and so specific IAS 41, so that CFOs, can generate financial information in accordance with the provisions of the Superintendency of Companies of Ecuador.